2021
DOI: 10.1108/ijm-03-2021-0173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of artificial intelligence on employees working in industry 4.0 led organizations

Abstract: PurposeThis study attempts to develop a practical understanding of the positive and negative employee experiences due to artificial intelligence (AI) adoption and the creation of technostress. It unravels the human resource development-related challenges with the onset of Industry 4.0.Design/methodology/approachSemi-structured interviews were conducted with 32 professionals with average work experience of 7.6 years and working across nine industries, and the transcripts were analyzed using NVivo.FindingsThe fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(131 citation statements)
references
References 73 publications
2
123
0
6
Order By: Relevance
“…The results of the study Wamba-Taguimdje et al (2020) have highlighted such AI benefits in organizations, and more specifically, its ability to improve performance at both the organizational (financial, marketing and administrative) and process levels. The study conducted by Malik et al (2021) also revealed that AI has a positive impact on work-related flexibility and autonomy, creativity and innovation and overall enhancement in job performance. Therefore: H1.…”
Section: Development Of Hypothesesmentioning
confidence: 89%
“…The results of the study Wamba-Taguimdje et al (2020) have highlighted such AI benefits in organizations, and more specifically, its ability to improve performance at both the organizational (financial, marketing and administrative) and process levels. The study conducted by Malik et al (2021) also revealed that AI has a positive impact on work-related flexibility and autonomy, creativity and innovation and overall enhancement in job performance. Therefore: H1.…”
Section: Development Of Hypothesesmentioning
confidence: 89%
“…Another critical aspect of a micro-organizational design is psychological sustainability at the workplace [31,32]. The issue closely related to the introduction of AI in an organization concerns technostress [32].…”
Section: Micro-organizational Variables Job Variety and Job Richnessmentioning
confidence: 99%
“…Another critical aspect of a micro-organizational design is psychological sustainability at the workplace [31,32]. The issue closely related to the introduction of AI in an organization concerns technostress [32]. Indeed, job risk and insecurity, underperformance, and the potential work overload, tightly connected to digitization, are looming over the psyche of a modern-day employee.…”
Section: Micro-organizational Variables Job Variety and Job Richnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging knowledge economy and technological interventions are changing the existing job profiles, hence the need for different skillsets and technological capabilities [ 9 ]. The creativity of members and the organization is essential in acquiring and using these abilities anew.…”
Section: Introductionmentioning
confidence: 99%